STRATEGI READING ALOUD DALAM MENUMBUHKAN MINAT MEMBACA SISWA DI KELAS IV SDN PANCORAN 07 PAGI (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2022)
This research discussed of the strategy of reading aloud for caused to emerge student interest in reading in the fourth grade of SDN Pancoran 07 Pagi. Because reading is one of the language skills that is needed in daily life. Especially in education. This research aimed to describe the factors that influence the reading interest of fourth-grade students at SDN Pancoran 07 Pagi and to explain the implementation of strategy reading aloud that has been carried out by the teacher for developing their reading interest. The method that has been used in this research is qualitative with a descriptive approach which means the researcher describes the results of the research that has been carried out in a narrative and costumized based on the conditions that already found out during the study. The results obtained through interviews, questionnaires, and documentation which tell that there are some factors that influenced students' interest in reading such as (1) external factors such as the role of parents, infrastructure, and the influence of teachers. (2) internal factor, which is their self like their ability to read. And the strategy of reading aloud that had been carried out by the teacher to the fourth-grade students was running effectively, students looked excited when the teacher asked them to read and some even took the initiative to read.